2020
DOI: 10.1055/s-0040-1716315
|View full text |Cite
|
Sign up to set email alerts
|

To Evaluate the Effect of Water Temperature and Duration of Immersion on the Marginal Accuracy and Microhardness of Provisional Restoration: An In Vitro Study

Abstract: Introduction Provisional restoration is a critical component of fixed prosthodontics treatment, which must satisfy many inter-relative factors such as biological, mechanical, and esthetic. These restorations should have accurate marginal adaptation and optimum strength to maintain functional demands. The present “in vitro” study was conducted to evaluate the effect of water temperature and duration of immersion, on the marginal adaptation and microhardness of four different commercially available provisional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Marginal fit depends on a number of factors, such as the tooth preparation design, method of measurement, impression technique, materials used, and thermomechanical aging (Angwarawong et al, 2020 ; Nawafleh et al, 2013 ; Ryu et al, 2020 ; Verma et al, 2020 ; Wu et al, 2021 ). It should be noted that in the fabrication of multiunit provisional FPDs, the marginal discrepancy is greater than that of single‐unit crowns due to polymerization shrinkage occurring at the pontic region (Balkenhol et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marginal fit depends on a number of factors, such as the tooth preparation design, method of measurement, impression technique, materials used, and thermomechanical aging (Angwarawong et al, 2020 ; Nawafleh et al, 2013 ; Ryu et al, 2020 ; Verma et al, 2020 ; Wu et al, 2021 ). It should be noted that in the fabrication of multiunit provisional FPDs, the marginal discrepancy is greater than that of single‐unit crowns due to polymerization shrinkage occurring at the pontic region (Balkenhol et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Digholkar et al [28] evaluated and compared the flexural strength and microhardness of provisional restorative materials fabricated utilizing rapid prototyping (RP), CAD-CAM and conventional method and reported a hardness value of 25.6 KHN (knoop hardness number) for CAD-CAM resin group. Verma et al [29] investigated the effect of water temperature and duration of immersion, on the marginal adaptation and microhardness of four different commercially available provisional restorative materials and concluded that the bisacryl composite materials exhibit superior surface microhardness. Diaz-Arnold et al [30] stated that bis-acryl composite resin materials exhibited superior microhardness over the traditional methyl methacrylate resins.…”
Section: Discussionmentioning
confidence: 99%